Dual pandemic of firearm injury and COVID-19 in Central and Southeastern Ohio: An interrupted time series analysis - Hannah Williams; Megan Armstrong; Robin Alexander; Jonathan Groner; Bo Lu; Sherri Kovach; Roxanna Giambri; Henry Xiang (PLoS ONE, 2026)
Firearm injuries increased as the United States faced the COVID-19 pandemic, a phenomenon some refer to as the “dual pandemic.” This study examines how one regional trauma system fared during the initial months of the dual pandemic and explores potential explanatory mechanisms of the surge of firearm injuries during the COVID-19 period. We used an interrupted time series model to compare quarterly data from 2016−2021 from the COTS (formerly known as the Central Ohio Trauma System) Regional Trauma Registry to examine the number of firearm injuries, mistriage rates of firearm-injured patients, injury intent, and cases with evidence of substance and alcohol abuse. Among 3,881 firearm-injured patients, demographic characteristics did not vary with respect to firearm injury, mistriage, mortality, substance use, or alcohol use. All but seven outcomes showed a significant level shift at the onset of the COVID-19 period, and all outcomes show a significant slope change during the COVID-19 period. All outcomes but one show a significant level shift at the end of the COVID-19 period, and all outcomes show a significant slope change from the conclusion of the COVID-19 period to the end of the study period. Wilcoxon ranked sum test shows no significant difference in the mean length of stay between the COVID-19 period and all other time included in the study period. This Midwest regional trauma system was affected by the dual pandemic of increased firearm injury during the COVID-19 lockdown. Findings highlight the roles of increased substance use and nonaccidental firearm injuries. Performance indicators reveal some evidence of strain within the region as the lockdown period progressed. Further research should identify region-specific causal mechanisms fueling the dual pandemic and compare the effects among urban, suburban, and rural communities.